Antibacterial nanocomposite hydrogels for superior biomedical applications: a Facile eco-friendly approach. Issue 19 (29th January 2015) - Raghavendra, Gownolla Malegowd; Jayaramudu, Tippabattini; Varaprasad, Kokkarachedu; Mohan Reddy, Goddeti Siva; Raju, Konduru Mohana
Abstract : Antibacterial Au-core Ag-shell Carbopol® 980 NF/Noveon® AA-1 polycarbophil nanocomposite hydrogels were fabricated by nucleation of Au 3+ and Ag + ions from the extracts of mint leaves by facile eco-friendly approach. Abstract : In this scientific paper, we report a facile and eco-friendly fabrication of antibacterial nanocomposite hydrogels of Au-core Ag-shell nanoparticles, embedded within Carbopol® 980 NF/Noveon® AA-1 polycarbophil acrylic acid polymeric matrix. The aim of the study was to investigate whether these nanocomposite hydrogels have the potential to be used for bacterial inactivation applications. The key feature was that, unlike the use of chemical reductants, auxiliary stabilizers and specialized expensive equipment, the Au-core Ag-shell nanoparticles (∼15 ± 3 nm) were synthesized utilizing aqueous mint leaf extracts. The developed hydrogels were characterized by Fourier transform infrared spectroscopy, transmission electron microscopy, scanning electron microscopy/energy-dispersive spectroscopy and thermogravimetric analysis. Swelling studies were performed in phosphate buffered saline (pH 7.4) solution. A sustained antibacterial study against E. coli (G−) and B. subtilis (G+) showed their excellent antibacterial efficiency, which suggested that the developed hydrogels are potential candidates for a wide range of biomedical applications.